Competing endogenous RNA networks in ovarian cancer - Roghaiyeh Derogar; Fatemeh Nejadi Orang; Mahdi Abdoli Shadbad (EXCLI Journal : Experimental and Clinical Sciences)
Epithelial ovarian cancer is responsible for the majority of ovarian malignancies, and its highly invasive nature and chemoresistant development have been major obstacles to treating patients with mainstream treatments. In recent decades, the significance of microRNAs (miRNAs), circular RNAs (circRNAs), long non-coding RNAs (lncRNAs), and competing endogenous RNAs (ceRNAs) has been highlighted in ovarian cancer development. This hidden language between these RNAs has led to the discovery of enormous regulatory networks in ovarian cancer cells that substantially affect gene expression. Aside from providing ample opportunities for targeted therapies, circRNA- and lncRNA-mediated ceRNA network components provide invaluable biomarkers. The current study provides a comprehensive and up-to-date review of the recent findings on the significance of these ceRNA networks in the hallmarks of ovarian cancer oncogenesis, treatment, diagnosis, and prognosis. Also, it provides the authorship with future perspectives in the era of single-cell RNA sequencing and personalized medicine.